The effect of a night shift nap on post-night shift performance, sleepiness, mood, and first recovery sleep: A randomized crossover trial - Patterson, P. Daniel; Hilditch, Cassie J.; Weaver, Matthew D.; Roach, David GL; Okerman, Tiffany S.; Martin, Sarah E.; Patterson, Charity G.; Weiss, Leonard S. (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVES ': 'This study aimed to test the effect of a 30-minute nap versus a 2-hour nap opportunity taken during a simulated night shift on performance, fatigue, sleepiness, mood, and sleep at the end of shift and during post-night shift recovery. ' ' METHODS ': 'We conducted a randomized crossover trial of three nap conditions (30-minute, 2-hour, and no-nap) during 12-hour simulated night shifts. We tested for differences in performance, fatigue, sleepiness, mood, and sleep during in-lab and at-home recovery. Performance was measured with the Brief Psychomotor Vigilance Test (PVT-B). Subjective ratings were assessed with single-item surveys. ' ' RESULTS ': 'Twenty-eight individuals consented to participate [mean age 24.4 (standard deviation 7.2) years; 53.6% female; 85.7% Emergency Medical Services clinicians]. PVT-B false starts at the end of the 12-hour night shift (at 07:00 hours) and at the start of in-lab recovery (08:00 hours) were lower following the 2-hour nap versus other conditions (P<0.05). PVT-B response time at +0 minutes post-recovery nap was poorer compared to pre-recovery nap for the no-nap condition (P=0.003), yet not detected for other nap conditions (P>0.05). Sleepiness, fatigue, and some mood states were lower at most hourly assessments during the in-lab recovery period following the 2-hour nap condition compared to the other conditions. Sleep during recovery did not differ by duration of night shift nap. ' ' CONCLUSIONS ': 'A 2-hour nap opportunity versus a 30-minute or no-nap opportunity is beneficial for performance, alertness, and mood post-night shift. No differences were detected in sleep during recovery.
Keywords: mood; nap; napping; night shift; randomized crossover trial; recovery sleep; shift performance; shift work; shift worker; sleepiness